IMPLEMENTASI KEBIJAKAN PENGEMBANGAN AKSESIBILITAS PARIWISATA PANTAI PASIR PUTIH WATES KABUPATEN REMBANG - Inayah, Destyana Kharismatul; Hanani, Retna; ., Kismartini (Journal of Public Policy and Management Review, 2024)
This research aims to analyze the implementation of tourism development policies at Pasir Putih Wates Beach by referring to the District Regulation. Rembang No. 12 of 2019. This research also identifies factors that influence policy implementation. Factors influencing policy implementation are presented by comparing four theories according to Van Horn and Van Metter, Edward III, Marilee Girdle and Mazmanian and Paul. The research method used is descriptive qualitative. Implementation of tourism development policies at Pasir Putih Wates Beach includes the development of public infrastructure, public facilities and tourism facilities. This research found problems in the implementation of District Regulations. Rembang No. 12 of 2019 covers the issue of budget limitations and management quality. The implementation of developing tourist accessibility for Pasir Putih Beach is not yet optimal because the management has not provided and has not developed a transportation system in the form of public transportation and supporting transportation facilities. Factors inhibiting the implementation of Pasir Putih Beach tourism development policies in Rembang Regency include standards and targets, resources and communication between organizations. The researcher's recommendation is that the management of Pasir Putih Wates Beach needs to collaborate with the private sector; Pasir Putih Sand Beach managers need to increase training so that the quality of managers increases; Pasir Putih Sand Beach management needs to collaborate with the Transportation Department to expand transportation routes to tourist attractions in Rembang Regency.